Analysis of Extracurricular Activities and Islamic Boarding School Culture in Character Formation in Vocational High School Students Case Study at SMK Al-Fatimiyah Karawang - Dhemas Fajar Handika; Amirudin; Acep Nurlaleli (al-Afkar, Journal For Islamic Studies, 2023)
Extracurricular activities are activities that are taught outside of learning. Which is prepared based on the needs of the institution, the need for knowledge, development, guidance and habituation of students to have knowledge and experience not only when in class, in school only by applying guidelines and based on values ​​and norms that are built both from central government education and built from within (formal, informal and non-formal educational institutions). The purpose of this study was to determine the implementation of character building through religious extracurricular activities and Islamic boarding school culture in formal secondary vocational institutions. SMK Al-Fathimiyah is a pesantren-based school in which there is a combination of the national curriculum with the local curriculum and the Islamic boarding school curriculum. This research is a field research using qualitative descriptive method. Data collection techniques were carried out through interviews and documentation. From research conducted by researchers, the results obtained are that the implementation of character building through extracurriculars and pesantren culture such as the Qur'an khotmil program, the cadre program driving the infaq movement of one thousand rupiahs every 1 week twice and the muhadhoroh program or habituation training activities such as tausyiah, leading tahlil procedures, as well as muamalah coaching.